Edukasi Tanda Bahaya Kehamilan dalam Meningkatkan Keselamatan Ibu dan Janin - Hasmidar, Hasmidar; Sulfakar, Sukmawati; Haerani, Haerani; Ilham, Nur Anisafauziah (Yayasan Inspirasi El Burhani, 2026)
Introduction: Pregnancy is a physiological process experienced by every woman of reproductive age, but it still carries the risk of complications. Danger signs in pregnancy are symptoms that indicate the possibility of serious complications, such as preeclampsia, antepartum hemorrhage, infection, or fetal growth problems. Objective: The purpose of this community service activity is to create a safe and healthy pregnancy and increase the knowledge of pregnant women and their families so that pregnant women and their families understand the danger signs during pregnancy. Method: The implementation of this community service activity began with several stages, starting with a lecture and continuing through a discussion and question-and-answer session. The first stage involved an opening and introduction, conveying the purpose of the outreach. The material was presented using simple language and visuals (posters/leaflets). The final stage focused on strengthening the outreach and emphasizing the importance of recognizing danger signs early and seeking immediate medical attention if they appear. Result: The results of the implementation of counseling activities on danger signs in pregnancy showed that pregnant women understood and increased their knowledge and were able to explain the meaning and signs of danger in pregnancy, pregnancy risk factors, dangers that can occur and preventing and anticipating dangers in pregnancy. Conclusion: The community service program, implemented in collaboration with the team, has successfully increased the understanding of pregnant women and their families regarding danger signs during pregnancy. Pregnant women can recognize important symptoms such as bleeding, excessive swelling, severe headaches, decreased fetal movement, high fever, and severe abdominal pain as conditions requiring immediate medical attention.